Leading Change in Health Systems Strategies for RN-BSN Students - Andresen, Kathy; Swanson, Charli (Open textbook library.)
Leading Change in Health Systems: Strategies for RN-BSN Students is designed for practicing nurses pursuing a Bachelor of Science in Nursing. This book is focused on building upon previous knowledge, skills and attitudes Registered Nurses (RNs) related to leadership in healthcare systems. Readers will be able to apply the theoretical knowledge gained from this course in their clinical practice environment.